Association between knowledge, attitude and practice regarding pertussis among medical and science-based students in a public university in Kuantan, Malaysia - Abdul Basir, Nur Amalina; A. Rahman, Nor Azlina (2018)
Pertussis, also known as whooping cough is an airborne respiratory disease caused by Bordetella pertussis infection. Increase in pertussis cases are noted despite the implementation of vaccination program worldwide. This study was conducted to explore the association between knowledge, attitude and practice regarding pertussis among the medical and science-based students in a public university in Kuantan, Malaysia. Using cross-sectional design, convenience sampling was applied to select the eligible participants. A newly developed questionnaire of four sections, namely sociodemographic data, knowledge, attitude and practice regarding pertussis was used to collect the data from 171 participants. The questionnaire had been checked for face and content validity. The results showed that there was significant correlation between knowledge and attitude, knowledge and practice, and also attitude and practice regarding pertussis among the medical and science-based students (r=0.511, p<0.001; r=0.344, p<0.001; r=0.293, p<0.001; respectively) indicated moderate to good positive correlation for knowledge and attitude, but fair positive correlation between knowledge and attitude with practice. This result shows that there is a possibility to improve the attitude and practice regarding pertussis if the community’s knowledge regarding the disease can be increased through more awareness and health promotion programme.